Effects of a tannin-rich legume (Onobrychis viciifolia) on in vitro ruminal biohydrogenation and fermentation - Toral, Pablo G.; Hervás, Gonzalo; Missaoui, Hajer; Andrés, Sonia; Giráldez, Francisco J.; Jellali, Saida; Frutos, Pilar (Spanish Journal of Agricultural Research, 2016)
There is still controversy surrounding the ability of tannins to modulate the ruminal biohydrogenation (BH) of fatty acids (FA) and improve the lipid profile of milk or meat without conferring a negative response in the digestive utilization of the diet. Based on this, an in vitro trial using batch cultures of rumen microorganisms was performed to compare the effects of two legume hays with similar chemical composition but different tannin content, alfalfa and sainfoin (Onobrychis viciifolia), on the BH of dietary unsaturated FA and on the ruminal fermentation. The first incubation substrate, alfalfa, was practically free of tannins, while the second, sainfoin, contained 3.5% (expressed as tannic acid equivalents). Both hays were enriched with sunflower oil as a source of unsaturated FA. Most results of the lipid composition analysis (e.g., greater concentrations of 18:2n-6, cis-9 18:1 or total polyunsaturated FA in sainfoin incubations) showed the ability of this tannin-containing legume to inhibit the BH process. However, no significant differences were detected in the accumulation of cis-9 trans-11 conjugated linoleic acid, and variations in trans-11 18:1 and trans-11 cis-15 18:2 did not follow a regular pattern. Regarding the rumen fermentation, gas production, ammonia concentration and volatile FA production were lower in the incubations with sainfoin (‒17, ‒23 and ‒11%, respectively). Thus, although this legume was able to modify the ruminal BH, which might result in improvements in the meat or milk lipid profile, the present results were not as promising as expected or as obtained before with other nutritional strategies.